2022
DOI: 10.17235/reed.2022.8553/2021
|View full text |Cite
|
Sign up to set email alerts
|

Definition of minimum procedures required to certify competence in gastrointestinal endoscopy using the Delphi method

Abstract: Introduction: As part of the training framework for medical specialities, it is vital to provide an agreed list of the type and number of practices involved in the professional work of a given specialty. Thus, the purpose of this study is to define a list of minimum procedures to ensure competence in Gastrointestinal Endoscopy based on a structured and agreed upon process, as well as to explore the opinions of experts in gastrointestinal endoscopy on the training of endoscopy physicians in Argentina and the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our findings suggest that to ensure access and capacity in rural areas, training opportunities and practice‐level supports should be available for PCPs in colonoscopy 26 . While general surgeons receive training in colonoscopy as part of their residency (typically at a recommended threshold of 50 colonoscopies), training programs generally recommend at least 100–200 procedures for competency, and a high number of completed procedures (275−500) are standard for colonoscopy specialists 66–68 . Prior literature has highlighted this tension between high‐quality colonoscopy procedures and access to screening 26,38,69–72 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings suggest that to ensure access and capacity in rural areas, training opportunities and practice‐level supports should be available for PCPs in colonoscopy 26 . While general surgeons receive training in colonoscopy as part of their residency (typically at a recommended threshold of 50 colonoscopies), training programs generally recommend at least 100–200 procedures for competency, and a high number of completed procedures (275−500) are standard for colonoscopy specialists 66–68 . Prior literature has highlighted this tension between high‐quality colonoscopy procedures and access to screening 26,38,69–72 .…”
Section: Discussionmentioning
confidence: 96%
“…26 While general surgeons receive training in colonoscopy as part of their residency (typically at a recommended threshold of 50 colonoscopies), training programs generally recommend at least 100-200 procedures for competency, and a high number of completed procedures (275−500) are standard for colonoscopy specialists. [66][67][68] Prior literature has highlighted this tension between high-quality colonoscopy procedures and access to screening. 26,38,[69][70][71][72] While there is conflicting research about quality of colonoscopy services performed by non-GI specialists, research supports the idea that colonoscopy performed by general surgeons and PCPs is safe overall, [34][35][36][37][38] and a recent study concluded screening colonoscopies performed by most physicians in rural and underserved areas met quality standards.…”
Section: Guideline Shift To Screening Initiation At Age 45mentioning
confidence: 99%